PERANCANGAN SISTEM INFORMASI MANAJEMEN DISTRIBUSI AGEN GAS ELPIJI BERBASIS WEB PADA PT. BAROKAH TIGA PUTRA - Kiranti, Mei Bunga; Mardiana, Ardi (Universitas Majalengka, 2025)
Barokah Tiga Putra is an LPG (Liquefied Petroleum Gas) agent in Majalengka Regency that distributes 3-kilogram LPG cylinders to more than 60 distribution bases. The current manual distribution process using Microsoft Excel leads to several problems, such as slow data access, recording errors, and the inability to monitor distribution in real time. This research aims to design and implement a web-based distribution management information system to improve efficiency, accuracy, and operational effectiveness. The system development method applied is Rapid Application Development (RAD), which consists of requirement planning, design, testing, and implementation stages. The implementation results show that the system successfully facilitates the management of base data, requests, deliveries, sales, and LPG receipts in an integrated manner. Furthermore, the system enables real-time monitoring of distribution, supporting agents in making strategic decisions. Therefore, the developed information system provides a practical solution to overcome the limitations of the previous manual distribution process.